The impact of human resources management practices on the policy of retaining faculty members in Jordanian universities in Jordan - Al-Tawalbeh, Nahar Ayed Abdulaziz (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the impact of practices on the impact of human resource management practices on the policy of retaining faculty members in private universities in the northern region in Jordan. A sample of (160) faculty members was chosen in private universities in the northern region in Jordan. The questionnaire was also built, which consisted of (41) paragraphs divided into two parts. The first relates to the dimensions of human resources management (planning to attract human resources, salaries and rewards, promotion to a higher scientific rank, developing the performance of faculty and evaluation) and the second (policy of retaining faculty members). ). After conducting the statistical methods for honesty and consistency of the questionnaire, it was applied to the members of the sample, and the results indicated that two dimensions of the dimensions of human resources management (planning to attract human resources, salaries and rewards) affect the policy of retaining faculty members while the dimensions of (promotion to a scientific rank) The highest development of the performance of faculty members and evaluation) did not affect the policy of retaining faculty members, and finally, the results showed that personal variables (experience and academic rank) did not affect human resource management practices. In light of these results, the researcher recommended the need to reconsider the policy of recruitment and recruitment in private universities in the northern region of Jordan.